Antibacterial and Mosquito Repellent Assay of Poly Herbal Oil - Marivignesh, R.; Hussain, M.I. Zahir; Vijayalakshmi, M.; Shajahan, A.; Kumar, S. Ramesh; Jameela, M. Sithi (Asian Journal of Biological and Life Sciences)
Aim: To evaluate the anti-bacterial and mosquito-repellant activities of herbal skin oil. Materials and Methods: The herbs used for the present study were washed well with tap water and weighed. 250 g each of the selected plant leaves was weighed and made into a paste using mortar and pestle. 500 mL of coconut oil was measured in a measuring cylinder transferred to a heating vessel and heated to low flam. The crushed leaf paste of Salvia rosmarinus, Azadirachta indica, and Ocimum basilicum were added to the coconut oil and heated to low flame for 15 min. The oil was cooled down to room temperature and filtered using a fine mesh filter. The filtered herbal oil was stored in glass bottles. Results and Discussion: In vitro antimicrobial activity of the Herbal oil was tested against 4 bacterial pathogens using the agar disc diffusion method. The zones of inhibition (in mm) were as follows: The highest inhibition was noted (19 mm) for Streptococcus pyogenes. The Medium inhibition was noted (17 mm) for Staphylococcus aureus and (15 mm) for Aeromonas hydrophila. The lowest inhibition was noted (14 mm) for Pseudomonas aeruginosa. The survey forms were collected from the randomly selected people after 10 days. About 40% of the surveyed people rated 5 out of 5 for the herbal oil. Another 40% of the surveyed people rated above 4.5 out of 5. The remaining 20% is rated above 4 for the herbal oil. From the survey, it is evident that the prepared herbal preparation is an effective mosquito repellent and is also 100% safe for the skin as a topical application. Conclusion: There are many chemical mosquito repellents seen in our market that cause side effects. This paper focuses on herbal mosquito repellent as well as poly herbal skin oil. In the present study, three herbs Salvia rosmarinus, Azadirachta indica, and Ocimum basilicum are selected to come up with an oil-based herbal formulation to be used as mosquito repellent and skin disease cure oil. The antibacterial activity of the herbal oil was good against pathogens causing skin infections and the mosquito-repellent efficiency of the polyherbal oil is assessed using the Survey method. From the survey conducted, it is evident that the prepared herbal preparation is an effective mosquito repellent and is also 100% safe for the skin as a topical application.
Keywords: Antibacterial activity; Ethnobotanical; Medicinal plants; Mosquito repellent